2014
DOI: 10.1890/14-0330.1
|View full text |Cite
|
Sign up to set email alerts
|

Apparent environmental synergism drives the dynamics of Amazonian forest fragments

Abstract: Abstract. Many contemporary ecosystems are likely to be affected by multiple environmental drivers, complicating efforts to predict future changes in those ecosystems. We studied long-term changes in forest dynamics and liana (woody vine) abundance and biomass in fragmented and intact forests of the central Amazon. We did so by contrasting trends in 33 permanent 1-ha plots near forest edges (plot center ,100 m from the nearest edge) with those in 36 1-ha plots in intact-forest interiors (150-3300 m from neare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 70 publications
3
30
0
Order By: Relevance
“…For instance, Laurance et al . () monitored 69 1‐ha permanent plots in forest edges and preserved forest interiors in the central Amazon from 1980 to 2012. They showed that mortality and recruitment of trees and lianas in edge and forest interiors have accelerated over time.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, Laurance et al . () monitored 69 1‐ha permanent plots in forest edges and preserved forest interiors in the central Amazon from 1980 to 2012. They showed that mortality and recruitment of trees and lianas in edge and forest interiors have accelerated over time.…”
Section: Discussionmentioning
confidence: 97%
“…In the Amazon basin, increased fire incidence, decreased carbon storage, and changes in forest dynamics caused by logging and fragmentation of forests are amplified by changes in the climate, with potential for dangerous feedback between impacts [26,77,78]. [2,79].…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…In the Amazon Basin where climate change is already having an impact, rising atmospheric CO2 and regional climate drivers influence forest fragments dynamics, tree community composition and distribution, tree mortality and aboveground biomass (Laurance et al 2014;Olivares et al 2015;Raghunathan et al 2015). Disturbances, such as hurricanes, cyclones, or typhoons, significantly affect forest structure and species composition in Central America (Anadoʹn et al 2014;Shiels & Gonzalez 2014;.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies focussed on South and Central America (n=26) followed by South Asia (n=24) and Africa (n=15) ( Miles et al 2004;Saatchi et al 2008); (2) changes in forest stand dynamics, including changes in forest cover, structure and composition (e.g., Anadoʹn et al 2014;Laurance et al 2014); and (3) changes in tree phenology (Gunarathne & Perera 2014;Hopkins & Graham 1987;Numata et al 2003). The temporal trend of publications indicates that climate change research in all tropical regions has increased over the last decade (Figure 2.2).…”
Section: Climate Change Impacts On Tropical Forestsmentioning
confidence: 99%
See 1 more Smart Citation